1998
DOI: 10.1046/j.1365-2419.1998.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability of the South Georgia marine ecosystem: biological and physical sources of variation in the abundance of krill

Abstract: Interannual variability is a characteristic feature of the Southern Ocean ecosystem, yet the relative roles of biological and physical processes in generating these fluctuations are unknown. There is now extensive evidence that there are years when there is a very low abundance of Antarctic krill (Euphausia superba) in the South Georgia area, and that this variation affects much of the ecosystem, with the most obvious impacts on survival and breeding success of some of the major predators on krill. The open na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
143
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(153 citation statements)
references
References 34 publications
9
143
0
1
Order By: Relevance
“…Therefore, a modeling approach is used in this study to further the understanding of krill transport via ocean currents. Recently, the idea of krill transport to South Georgia from an upstream source was tested with modeling studies using a composite flow field Murphy et al, 1998). These studies show that the currents associated with the ACC can transport particles from the Antarctic Peninsula to South Georgia in 140-160 days.…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a modeling approach is used in this study to further the understanding of krill transport via ocean currents. Recently, the idea of krill transport to South Georgia from an upstream source was tested with modeling studies using a composite flow field Murphy et al, 1998). These studies show that the currents associated with the ACC can transport particles from the Antarctic Peninsula to South Georgia in 140-160 days.…”
Section: Article In Pressmentioning
confidence: 99%
“…Recent reviews suggest that krill may not be considered passively drifting particles, but that their behavior and swimming capabilities as adults may let them move to areas of their choice (Nicol, 2003a,b). However, it has been shown that advection by ocean currents is a major factor in determining the large-scale distribution (Marr, 1962;Murphy et al, 1998). Unfortunately, there have only been few studies of the potential effects of behavior in analyses of large-scale distribution (Murphy et al, 2004a).…”
Section: Drifter Initialization and Implementationmentioning
confidence: 99%
“…The krill population at South Georgia is believed not to be self-sustaining (Everson, 1984) but to be maintained instead by oceanic transport of krill from recognised breeding grounds upstream of South Georgia in the vicinity of the Antarctic Peninsula, the South Orkney Islands and the Weddell Sea (e.g. Everson, 1977;Murphy et al, 1998) [ Fig. 1(a)].…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the scales and links between physical and biological processes impacting zooplankton in both polar ecosystems is critical, as the dominant species are relatively long lived (copepods 1-4 years, Arctic euphausiid species 3-4 years, Antarctic euphausiids >5 years, and possibly as many as 9 years) (Ikeda and Thomas, 1987;Murphy et al, 1998;Falk-Petersen et al, 2009). These zooplankton are important grazers on microplankton and ice algae, and form important couplings to the upper trophic levels.…”
Section: Zooplanktonmentioning
confidence: 99%
“…Investigations of zooplankton transport in the Southern Ocean have focused primarily on Antarctic krill, given their importance as a key link in the Antarctic marine food web and as the focus of a commercial fishery (e.g., Hofmann et al, 1998;Murphy et al, 1998Murphy et al, , 2004aMurphy et al, , 2004bHofmann and Murphy, 2004;Fach and Klinck, 2006;Piñones et al, 2013aPiñones et al, , 2013b. Krill have a heterogeneous circumpolar distribution, with about 70% of the stock occurring between 0 and 90°W, including the open waters of the Antarctic Circumpolar Current in the Atlantic sector (Scotia Sea) and the western side of the Antarctic Peninsula (Atkinson et al, 2008).…”
Section: Impacts Of Advection On Zooplankton In the Antarcticmentioning
confidence: 99%